ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA PADA MATERI ARITMATIKA SOSIAL BERDASARKAN PERBEDAAN GENDER - Helma Mustika; Puji Astuti; Sri Yunita Ningsih; Gema Hista Medika; Hepni Tri Arjelia; Ramadhani Fitri (Ensiklopedia of Journal, 2022)
This research begins with the results of interviews and observations which show that the value of students' mathematical critical thinking skills in class VII SMP Negeri 1 Sungai Lala is still low and there are differences between female students and male students in the process of solving the exercises given by the teacher. The purpose of this study was to determine whether there is a difference between critical thinking skills based on gender differences. This type of research is descriptive qualitative research. The subjects in this study were four students consisting of two female students and two male students, in which the four students were selected based on their critical thinking ability scores. The research instruments were questionnaire sheets and test questions. The data obtained will be analyzed by means of data reduction, data presentation, and data verification. Based on the results of the study showed that the results of the questionnaire percentage of critical thinking skills for female students were higher than for male students. The percentage results obtained were 50.77% for female students and 49.23% for male students. The completion of critical thinking ability test questions between female students and male students has differences. Female students have been able to master the five indicators of critical thinking skills in solving test questions, while for male students there are two indicators of critical thinking abilities that they have not yet mastered. In terms of conclusion, that female students have excellent critical thinking skills while male students have good critical thinking skills.